Nine Irish plays for voices - Grennan, Eamon, 1941- (New York : Fordham University Press, 2023)
A vibrant collection of short plays bringing Irish history and culture alive through an extraordinary collage of documents, songs, poems, and textsIn Nine Irish Plays for Voices award-winning poet Eamon Grennan delves deep into key Irish subjects--big, small, literary, historical, political, biographical--and illuminates them for today's audiences and readers. These short plays draw from original material centering on important moments in Irish history and the formation of the Irish Republic, such as the Great Famine and the Easter Rising; the lives of Irish literary figures like Yeats, Joyce, and Lady Gregory; and the crucial and life-changing condition of emigration. The rhythmic, musical, and vivid language of Grennan's plays incorporates traditional song lyrics, lines of Irish poetry, and letters and speeches of the time. The result is a dramatic collage that tells a story through the voices of characters contemporary to the period of the play's subject. By presenting subjects through the dramatic rendering of the human voice, the plays facilitate a close, intimate relationship between players and the audience, creating an incredibly powerful connection to the past. Historical moments and literary figures that might seem remote to the present-day reader or audience become immediate and emotionally compelling. One of the plays, Ferry, is drawn entirely from the author's imagination. It puts unnamed characters who come from the world of twentieth century Ireland on a boat to the underworld with the philosopher Ludwig Wittgenstein. On their journey the five strangers, played by two voices, tell stories about their lives, raising the question of how language both captures and transforms lived experience. Addressing the Great Famine, Hunger uses documentary evidence to give audiences a dramatic feel for what has been a silent and traumatic element in Irish history. NORAMOLLYANNALIVIALUCIA: The Muse and Mr. Joyce is a one-woman piece that depicts James Joyce's wife as an older woman sharing her memories and snippets from the works of her husband. Also included in this rich volume is the author's adaptation of Synge's Aran Islands, as well as Emigration Road, History! Reading the Easter Rising, The Muse and Mr. Yeats, The Loves of Lady Gregory, and Peig: An Ordinary Life.
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Part One -- Hunger (2010) -- Emigration Road (2011) -- History! Reading the Easter Rising (2016) -- Part Two -- The Muse and Mr. Yeats (2013) -- Noramollyannalivialucia: The Muse and Mr. Joyce (2014) -- J. M. Synge's The Aran Islands (2009) -- The Loves of Lady Gregory (2018) -- Peig: An Ordinary Life (2020) -- Coda -- Ferry (2012) -- Acknowledgments
Description based on online resource; title from digital title page (viewed on January 17, 2023).
eBooks on EBSCOhost
Keywords: Irish drama -- 21st century; Théâtre irlandais -- 21e siècle.; DRAMA / General; Irish drama; 2000-2099; Drama; Drama; Théâtre.